CLASSIFICATION AND MODERN TREATMENT OF TYPE 2 DIABETES MELLITUS - А. Б. Ахмедова (Web of Journals Publishing, 2024)
Diabetes mellitus is one of the main problems of modern medicine, which is primarily due to the high risk of developing cardiovascular complications, as well as early disability of patients and mortality. The progressive increase in the number of patients with diabetes mellitus and the high mortality rate among them dictate the need for further study of the causes and mechanisms of the development of the disease. Despite the availability of modern diagnostic methods, as well as the development of new therapeutic and preventive measures, the number of cases of early disability and mortality continues to increase among patients with diabetes mellitus of working age. The main reason for such outcomes is the development of chronic cardiovascular complications.
Keywords: diabetes mellitus, pathogenesis of diabetes mellitus, classification of diabetes mellitus, clusters, complications of diabetes mellitus, prognosis of diabetes mellitus.